The power of habitus - participation in political parties - Meßmer, Anna-Katharina; Banaszczuk, Yasmina (Momentum Quarterly, 2013)
The demographic and structural change in Germany does not stop at political parties: In order to stop their continuing decrease in members their structures must become more diverse and open. This paper examines how new forms of participation and diversity measures can work in the context of social inequalities. Furthermore, we will consider the challenge to crack system immanent structures open for previously excluded members. The Social Democratic Party of Germany (SPD) will be used as an example. With its party reform in 2011, SPD declared the goal to become the „most modern party in Europe“. This paper analyses remaining including and excluding circumstances that keep marginalised groups from joining and getting promoted in the SPD. The theoretical frameworks used are gender and social inequalities theories.
Keywords: political parties; inclusion; inequality; gender; diversity